The effect of work environment and health, work safety on employee performance - Lindawati, Lindawati; Nurfi, Nurfi; Nurjihan, Nisrina; Haryadi, Didit (Institute of Computer Science (IOCS), 2024)
Employee performance is an essential factor influencing success. In an organization, this is one of the most critical functions of a company. This study aims to determine the variables that affect employee performance and develop a theoretical basis and research model. This study used an associative descriptive quantitative method with a population of 56 respondents drawn into a sample using non-probability sampling, using the saturated sampling / total sampling method. Data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis of the work environment does not affect employee performance. Thus, the second hypothesis states that occupational health safety significantly influences employee performance. The third hypothesis is that employee performance is influenced by the work environment and occupational health safety, which can simultaneously improve employee performance. This research is expected to make theoretical contributions to the literature in this context, certainly in the context of human resource management.